Perioperative Considerations in Osteogenesis Imperfecta: A 20-Year Experience with the Use of Blood Pressure Cuffs, Arterial Lines, and Tourniquets - Kirsten E. Ross; Joseph T. Gibian; Christy J. Crockett; Jeffrey E. Martus (MDPI AG, 2020)
Osteogenesis imperfecta (OI) is a rare genetic connective-tissue disorder with bone fragility. To avoid iatrogenic fractures, healthcare providers have traditionally avoided using non-invasive blood pressure (NIBP) cuffs and extremity tourniquets in the OI population in the perioperative setting. Here, we hypothesize that these procedures do not lead to iatrogenic fractures or other complications in patients with OI. A retrospective study of all children with OI who underwent surgery at a single tertiary care children's hospital from 1998 to 2018 was performed. Patient positioning and the use of NIBP cuffs, arterial lines, and extremity tourniquets were documented. Fractures and other complications were recorded. Forty-nine patients with a median age of 7.9 years (range: 0.2-17.7) were identified. These patients underwent 273 procedures, of which 229 were orthopaedic operations. A total of 246 (90.1%) procedures included the use of an NIBP cuff, 61 (22.3%) an extremity tourniquet, and 40 (14.7%) an arterial line. Pediatric patients with OI did not experience any iatrogenic fractures related to hemodynamic monitoring or extremity tourniquet use during the 20-year period of this study. Given the benefits of continuous intra-operative hemodynamic monitoring and extremity tourniquets, we recommend that NIBP cuffs, arterial lines, and tourniquets be selectively considered for use in children with OI.